Integration of Knowledge to Reduce Risks from Hydrocarbon Spills in Water Sources - Verónica Zapata Gómez; Manuela Cortés Cano; Olga Lucía Amaya Moncada; Laura Osorio Cano; Edna Margarita Rodríguez Gaviria (Revista de Estudios Latinoamericanos sobre Reducción del Riesgo de Desastres, 2022)
Located on the western outskirts of Medellín, San Cristobal Village has been exposed to a variety of risk factors, since early 21st century, due to hydrocarbons contamination of its water resources. This contributes to an increase of the vulnerability, caused by disinformation; lack of a risk management plan, and governmental and private entities in the risk management committees. The applied methodology integrates: a compilation of information throughout databases, news, surveys, and participative workshops; participants identification; analysis to causes which are hazardous to the potable water service; territorial analysis; cartography elaboration analysis; and, educative measures implementation. The application of this methodology has allowed for, raise a discussion about the conditions of vulnerability generated by the disarticulation with local development planning, and by the surveillance and advisory of the community problems, besides the proposal of prospective and corrective measures for risk reduction.